Value creation analysis using atomic business models: The case of Digikala e-retailer – Part B. Issue 2 (November 2020) - Hanafizadeh, Payam; Mehri, Saeedeh; Hasanabadi, Hamid
One of the reasons most startups fail, despite their growing number, is the inability and lack of flexibility of their business models in responding to market changes. In addition, due to the uncertainty of the startups' environment, it is difficult to gain competitive advantage; startups need to continuously change their business models. One of the most common electronic business models is the electronic retailer. Despite the many challenges facing e-retailers due to market changes and customer preferences, Digikala has been ranked as the most popular and most visited website and has managed to gain over 85% of the Iranian retail market share. The purpose of this study is to analyze the value creation in Digikala in order to answer the following questions: Through which atomic business model can business value be realized? What change strategies should be applied to be able to provide a unique and stable value and be successful?